Phytochemical and Pharmacological potential of Flemingia Roxb. ex W.T.Aiton (Fabaceae) - Kavita Ghalot,; V.K. Lal,; S. Jha, (International Journal of Phytomedicine, 2011)
The Flemingia genus is an important source of medicinal natural products, particularly Flavonoids and steroids. The collected information is an attempt to cover the more recent developments in the ethnobotany, pharmacology and phytochemistry of this genus. The review includes 39 references on the genus Flemingia, and comprises ethnopharmacology, morphology, phytoconstituents, pharmacological reports, clinical study and adverse effects of the prominent species of Flemingia. A few species of this genus have medicinal value, among these, F.strobilifera ,F.macrophylla, F.chappar (Fabaceae) have been traditionally used in the treatment of epilepsy, insomnia, ulcer, pain ,swelling. Despite a long tradition of use of some species, the genus has not been explored properly. In the concluding part, the future scope of Flemingia species has been emphasized with a view to establish their multifarious biological activities and mode of action. The information summarized here is intended to serve as a reference tool to practitioners in the fields of ethnopharmacology and natural products chemistry.